The Impact of Initial COVID-19 Episode Inflammation Among Adults on Mortality Within 12 Months Post-hospital Discharge - Mainous, Arch G.; Rooks, Benjamin J.; Orlando, Frank A. (Frontiers in Medicine, 2022)
Background: Inflammation in the initial COVID-19 episode may be associated with post recovery mortality. The goal of this study was to determine the relationship between systemic inflammation in COVID-19 hospitalized adults and mortality after recovery from COVID-19. Methods: An analysis of electronic health records (EHR) for patients from 1 January, 2020 through 31 December, 2021 was performed for a cohort of COVID-19 positive hospitalized adult patients. 1,207 patients were followed for 12 months post COVID-19 episode at one health system. 12-month risk of mortality associated with inflammation, C-reactive protein (CRP), was assessed in Cox regressions adjusted for age, sex, race and comorbidities. Analyses evaluated whether intravenous steroids in the hospital or steroids prescribed upon discharge were associated with later mortality. Results: Elevated CRP was associated with an increased mortality risk after recovery from COVID-19. This effect was present for both unadjusted (HR=1.60; 95% CI 1.18, 2.17) and adjusted analyses (HR=1.61; 95% CI 1.19, 2.20) when CRP was split into high and low groups at the median. Intravenous dexamethasone given during the initial hospitalization episode was associated with an increased risk of mortality (adjusted HR=1.46; 95% CI 1.07, 1.98). In contrast, oral steroid prescriptions at discharge were found to be associated with a lower risk of death post-discharge (adjusted HR=0.49; 95% CI 0.73, 0.94). Discussion: Hyperinflammation present with severe COVID-19 is associated with an increased mortality risk after hospital discharge. Although suggestive, treatment with anti-inflammatory medications like steroids upon hospital discharge is associated with a decreased post-acute COVID-19 mortality risk.